PENGEMBANGAN MEDIA GOOGLE SITES BERBASIS PROBLEM BASED LEARNING PADA MATERI SISTEM SIRKULASI KELAS XI SMA - Rany Masriana Pandiangan; Aminuddin Prahatama Putra (Bioedukasi Jurnal Pendidikan Biologi, 2025)
Learning the circulatory system in Grade XI high school often encounters challenges due to the lack of interactive media that align with the characteristics of 21st-century learners. Students require technology-based media to help them understand abstract biological concepts such as the circulatory system. This study aims to describe the validity and practicality of Google Sites–based learning media developed using the Problem-Based Learning (PBL) model on circulatory system material. The research employed the 4D development model, involving two experts for validation and nine students for practicality testing. Data were collected using validity and practicality instruments. The results showed that the PBL-based Google Sites media achieved a validity score of 91.07% (“very validâ€) and a practicality score of 86.44% (“very practicalâ€). These findings indicate that the developed learning media is feasible for use in teaching the circulatory system to Grade XI high school students. This study provides an innovative solution to address the challenges of circulatory system learning through the integration of interactive and technology-oriented media suited to modern learning needs.